2016
DOI: 10.1111/gfs.12247
|View full text |Cite
|
Sign up to set email alerts
|

Effects of replacing timothy silage by alsike clover silage on performance, carcass traits and meat quality of finishing Aberdeen Angus and Nordic Red bulls

Abstract: The objective of the study was to determine the effects of silage plant species and cattle breed on performance and meat quality of finishing bulls. A feeding experiment was conducted using thirty Aberdeen Angus (AA) and thirty Nordic Red (NR) bulls. Both breeds were randomly allotted to three experimental diets. The composition (g kg−1 dry matter) of the diets was as follows: (i) timothy silage (TS) (650) and barley (350); (ii) TS (325), alsike clover silage (AS) (325) and barley (350); and (iii) AS (650) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 53 publications
1
7
0
Order By: Relevance
“…In recent Finnish experimental data sets for dairy bulls fed grass silage and grain based diets and housed in similar environments (Huuskonen et al 2016(Huuskonen et al , 2017a(Huuskonen et al , 2017b, the average DM intake of the bulls was roughly at the same level as in the present experiment. In an earlier meta-analysis Huuskonen et al (2013) found that DM intake of growing and finishing cattle can be predicted from body weight and diet composition with a reasonable accuracy.…”
Section: Discussionsupporting
confidence: 64%
“…In recent Finnish experimental data sets for dairy bulls fed grass silage and grain based diets and housed in similar environments (Huuskonen et al 2016(Huuskonen et al , 2017a(Huuskonen et al , 2017b, the average DM intake of the bulls was roughly at the same level as in the present experiment. In an earlier meta-analysis Huuskonen et al (2013) found that DM intake of growing and finishing cattle can be predicted from body weight and diet composition with a reasonable accuracy.…”
Section: Discussionsupporting
confidence: 64%
“…The bulls were fed a total mixed ration ad libitum (proportionate refusals of 5%). Mineral and vitamin composition of the mineral-vitamin mixture (Kasvuape E-Hiven, A-Rehu Ltd., Seinäjoki, Finland) is fully described by Huuskonen et al (2017). Two HO bulls (one SALT and one ACID) were excluded from the study due to pneumonia and one HO bull (SALT) due to several occurrences of bloat.…”
Section: Feeds Feeding and Experimental Designmentioning
confidence: 99%
“…Mineral and vitamin composition of the mineral-vitamin mixture (Kasvuape E-Hiven, A-Rehu Ltd., Seinäjoki, Finland) is fully described by Huuskonen et al (2017). The bulls were fed a total mixed ration ad libitum (proportionate refusals of 5%).…”
Section: Feeds Feeding and Experimental Designmentioning
confidence: 99%